THE URGENCE OF CULTURAL INVESTMENT AND THE APPLICATION OF DIGITAL LITERATURE TO THE COMMUNITY - Rofia Masrifah; Titi Mildawati; A Mustika Abidin (Jurnal Teknologi Pendidikan Madrasah, 2022)
Digital literacy is the interests, attitudes and abilities of individuals who directly use digital technology and communication tools to access, manage, integrate, analyze and evaluate information, build new knowledge, create and communicate with others in order to participate effectively in society. The implementation of education is held as a process of civilizing and empowering students that lasts a lifetime. This principle is in accordance with the general provisions of the 2003 National Education System Law Article 1 paragraph 1 which states that education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control